Bibliometric study of soluble guanylate cyclase stimulators in cardiovascular research based on web of science from 1992 to 2021 - Jia, Xiao-Yan; Liu, Yong-Ming; Wang, Yong-Fei; An, Jin-Yang; Peng, Ke-Ling; Wang, Hua (Frontiers in Pharmacology, 2022)
Background: Several studies have shown that soluble guanylate cyclase (sGC) stimulators have cardiovascular (CV) benefits. However, few bibliometric analyses have examined this field systematically. Our study aimed to examine the publications to determine the trends and hotspots in CV research on sGC stimulators. Methods：Publications on sGC stimulators in CV research were retrieved from the Web of Science Core Collection. VOSviewer and CiteSpace visualization software were used to analyze publication trends, countries (regions) and institutions, journals and cited journals, authors and cited references, as well as keywords. Results: A total of 1212 literatures were obtained. From its first appearance in 1992 to 2021(based on WOSCC record), the overall volume of publications has shown a gradual increasing trend. Nearly one-third were authored by American scholars, and most were published in Circulation, Circulation Research, and Proceedings of the National Academy of Sciences of the United States of America. Bayer Agency in Germany was the leading driving force, and has a high academic reputation in this field. Stasch JP has published the most related articles and been cited most frequently. Half of the top 10 co-cited references were published in the leading highly co-cited journal Circulation and New England Journal of Medicine. “NO”, “allosteric regulation” and “free radicals” were the focus of previous research, “chronic thromboembolic pulmonary hypertension”, “pulmonary hypertension” and “heart failure” were the main research hotspots. The key words “chronic thromboembolic pulmonary hypertension”, “Pulmonary hypertension”, “preserved ejection fraction” and “heart failure” appeared most recently as research frontiers. Conclusion: The research in the CV field of sGC stimulators was relatively comprehensive, and there was a close relationship among countries, research institutions and authors, but it is still in the exploratory stage in the treatment of CV disease. At present, most studies focus on the results of clinical trials. sGC stimulators in the treatment of heart failure, especially heart failure with preserved ejection fraction, may be the hotpots and frontier at present and in the future, and should be closely monitored.